Solitary fibrous tumor of the upper lip: an uncommon case presentation - Pontes, Hélder Antônio Rebelo; Amaral, Carina Barros do; Menezes, Esther Castro de; Lameira, Igor Mesquita; Gomes , Nathalia Rodrigues; Neto, Nicolau Conte; Sousa, Rosa Hiolanda Abreu de; Uchoa, Sue Ann Lavareda Correa; Foscaldo, Tatiana Ferreira; Pontes, Flávia Sirotheau Correa (Journal of Oral Diagnosis, 2025)
Solitary Fibrous Tumor (SFT) is a rare mesenchymal neoplasm, account approximately 3% of mesenchymal tumors in the oral cavity. We present the case of a 65-year-old female patient with a painless swelling in the left upper lip. Clinical examination revealed a firm, smooth-surfaced submucosal lesion without ulceration, non-tender on palpation, and exhibiting a slightly yellowish hue. Computed tomography demonstrated a well-defined, isodense mass measuring 25 mm in diameter, with no evidence of bone invasion. The lesion was surgically excised, and histopathological analysis confirmed the diagnosis of SFT, supported by positive immunohistochemical staining for CD34 and STAT6. The tumor was classified as low risk for metastasis, and the patient demonstrated favorable postoperative recovery. The patient remains under follow-up with the medical team and has been recurrence-free for 07 months. This case underscores the rarity of oral cavity SFT and emphasizes the importance of comprehensive differential diagnosis to guide effective management and reduce recurrence risk.